Differentiated Learning Innovations to Increase Early Childhood Creativity through Loose Part Media - Nurhayati, Puput; Tumbularani (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to explore innovations in differentiated learning using loose part media to improve early childhood creativity at RA Al-Hikmah Beringin Subdistrict and provide understanding to teachers about the application of differentiated learning. This research method was conducted through classroom action research in class B at RA Al-Hikmah Beringin District with the participation of 15 students, consisting of 6 male students and 9 female students. The data analysis approach used included descriptive qualitative and descriptive quantitative, while data collection techniques involved observation, interviews, and documentation. The study consisted of two cycles with four stages, namely planning, implementation, observation, and reflection. Each cycle applied a different learning approach with a focus on children's learning readiness, learning interest and learning profile. The research implementation process involved four stages, namely content, process, product, and learning environment. The results showed that at the pre-cycle stage, the development of children's creativity through differentiated learning with loose parts media was still low, with an average of 26.6%. In Cycle I, there was an increase in children's creativity development of 53.3%, while in Cycle II the increase was more significant reaching 80%. These findings make an important contribution to the development of inclusive and interesting learning methods for early childhood.